Predicting Translation Initiation Rates for Designing Synthetic Biology - Reeve, Benjamin; Hargest, Thomas; Gilbert, Charlie; Ellis, Tom (Frontiers in Bioengineering and Biotechnology, 2014)
In synthetic biology, precise control over protein expression is required in order to construct functional biological systems. A core principle of the synthetic biology approach is model-guided design and, based on biological understanding of the process, models of prokaryotic protein production have been described. Translation initiation rate is a rate-limiting step in protein production from mRNA and is dependent on the sequence of the 5’-untranslated region (UTR) and the start of the coding sequence. Translation rate calculators are programs that estimate protein translation rates based on the sequence of these regions of an mRNA and as protein expression is proportional to the rate of translation initiation, such calculators have been shown to give good approximations of protein expression levels. In this review, three currently available translation rate calculators developed for synthetic biology are considered, with limitations and possible future progress discussed.